Amyloid β–dependent neuronal silencing through synaptic decoupling - Yonghai Zhang; Hsing-Jung Chen-Engerer; Kuan Zhang; Benedikt Zott; Zsuzsanna Varga; Yang Chen; Xiaowei Chen; Hongbo Jia; Bert Sakmann; Israel Nelken; Arthur Konnerth (Proceedings of the National Academy of Sciences, 2025)
Amyloid β (Aβ)-dependent circuit dysfunction in Alzheimer’s disease (AD) is determined by a puzzling mix of hyperactive and inactive (“silent”) brain neurons. Recent studies identified excessive glutamate accumulation as a key Aβ-dependent determinant of hyperactivity. The cellular mechanisms underlying neuronal silence depend on both Aβ and tau protein pathologies, with an unknown role of Aβ. Here, by using single-cell-initiated rabies virus (RV) tracing in mouse models of β-amyloidosis, we demonstrate that the presynaptic connectivity of silent, but not that of hyperactive, neurons is severely disrupted. Furthermore, silent neurons display a major spine loss and strongly suppressed synaptic activity. Thus, we suggest that synaptic decoupling is an Aβ-dependent cellular mechanism underlying progressive neuronal silencing and a critical factor for the cognitive impairments encountered in AD.